Breaking the barriers of submission a road to hope... (Revista Electrónica REDINE, 2018)
In order to assist in creating an awareness of equity, commenced in the recognition of women as a social person with rights and obligations, whose femininity has to be seen from a perspective that favors the growth of a more humane society; This paper reflects on the results of the research of gender studies, which for some years has been developing the author (Ordóñez, 2011, 2012) and is oriented to understand this anomalous situation in which a woman, subject to periodic situations tort, remains tied to physical or psychological pain that it causes humiliation, deprived of the satisfaction and urges that an attitude of submission to their partner. From the busy trail concludes that the difficulty facing the battered woman to free the victim status, cannot be explained by a single argument, however, the process of thinking and discerning about this sad reality, warrants of a comprehensive analysis, the final conclusion emanating from the diverse perspectives that throughout time have tried to understand and stop the underlying inequalities in gender relations.
Keywords: gender relations; gender violence; domestic violence